Internal Control System Landscape of a State University in a Highly Urbanized City - Nillos, Jet; Libo-on, Rowena (Journal of Interdisciplinary Perspectives, 2024)
This qualitative case study approach allows for a detailed exploration of internal control systems in HEIs, focusing on their implementation and functioning within various institutional settings. By employing in-depth interviews, the study gathered comprehensive information on the internal control processes of a government-funded HEI in a highly urbanized city. The key findings reveal that the hiring process is thorough, ensuring fairness, transparency, and compliance with governmental and institutional regulations. The training process is well-organized within the institution’s professional development framework. The procurement process is highly structured and transparent, emphasizing compliance and accountability. The budget process is formalized and governed by strict frameworks, and the payroll process is meticulously regulated to ensure accuracy, compliance, and transparency. Furthermore, the study underscores the need for public HEIs to continuously adapt their policies and procedures to the complex and evolving regulatory landscape, which is both time-consuming and costly. To enhance financial governance, ensure regulatory compliance, and maintain transparency and accountability, the study recommends training on the importance of following Commission on Audit (COA) guidelines and the Government Accounting Manual (GAM).